Polymorphic genes of detoxification and mitochondrial enzymes and risk for progressive supranuclear palsy: a case control study - Potts Lisa F; Cambon Alex C; Ross Owen A; Rademakers Rosa; Dickson Dennis W; Uitti Ryan J; Wszolek Zbigniew K; Rai Shesh N; Farrer Matthew J; Hein David W; Litvan Irene (BMC, 2012)
Abstract Background There are no known causes for progressive supranuclear palsy (PSP). The microtubule associated protein tau (MAPT) H1 haplotype is the major genetic factor associated with risk of PSP, with both oxidative stress and mitochondrial dysfunction also implicated. We investigated whether specific single nucleotide polymorphisms (SNPs) in genes encoding enzymes of xenobiotic detoxification, mitochondrial functioning, or oxidative stress response, including debrisoquine 4-hydroxylase, paraoxonase 1 and 2, N-acetyltransferase 1 and 2 (NAT2), superoxide dismutase 1 and 2, and PTEN-induced putative kinase are associated with PSP. Methods DNA from 553 autopsy-confirmed Caucasian PSP cases (266 females, 279 males; age at onset 68 ± 8 years; age at death 75 ± 8) from the Society for PSP Brain Bank and 425 clinical control samples (197 females, 226 males; age at draw 72 ± 11 years) from healthy volunteers were genotyped using Taqman PCR and the SequenomiPLEX Gold assay. Results The proportion of NAT2 rapid acetylators compared to intermediate and slow acetylators was larger in cases than in controls (OR = 1.82, p < 0.05). There were no allelic or genotypic associations with PSP for any other SNPs tested with the exception of MAPT (p < 0.001). Conclusions Our results show that NAT2 rapid acetylator phenotype is associated with PSP, suggesting that NAT2 may be responsible for activation of a xenobiotic whose metabolite is neurotoxic. Although our results need to be further confirmed in an independent sample, NAT2 acetylation status should be considered in future genetic and epidemiological studies of PSP.